ANALISIS RISIKO BISNIS DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PT INKA MADIUN - Rispantyo, Danik Karyawati, Y. Djoko Suseno & (Universitas Slamet Riyadi, 2017)
This research aims to determine whether there is significant influencebetween (1) Business Risk and Firm Size to Profitability, (2) Business Risk,Firm Size, and Profitability to Capital Structure, and whether Profitabilitymediates Business Risk and Firm Size at PT INKA Madiun.This researchused secondary data obtained from financial reports of PT INKA Madiun from2003 to 2015 presented in rupiah. Data analysis technique used is PathAnalysis with classical assumption test, t test, F test and Determination test.Conclusion. (1) Hypothesis â€œThe Business Risk influences the Profitability inPT INKA Madiunâ€ is true, (2) Hypothesis â€œThe Firm Size influences theProfitability in PT INKA Madiunâ€ is not true, (3) Hypothesis â€œThe BusinessRisk influences the Capital Structure in PT INKA Madiunâ€ is not true, (4)Hypothesis â€œThe Firm Size influences the Capital Structure in PT INKAMadiunâ€ is true, (5) Hypothesis â€œThe Profitability influences the CapitalStructure in PT INKA Madiunâ€ is true, (6) Hypothesis â€œThe Profitabilitymediates the Business Risk and Capital Structure in PT INKA Madiunâ€ is nottrue; (7) Hypothesis â€œThe Profitability mediates the Firm Size and CapitalStructure in PT INKA Madiunâ€ is true.Keywords: business risk, firm size, profitability, capital structure